Influence of surgically inducted weight loss on sexual function of obese male patients - literature overview - Jung, Maximilian; Jung, Magdalena; Woźniak, Kinga; Sysło, Oliwia; Jung, Samuel; Gardian-Baj, Monika; Hedesz, Patryk; Żuk-Łapan, Aleksandra; Doryń, Aleksandra; Szczerbiak, Alicja (Journal of Education, Health and Sport, 2024)
Introduction: Obesity is one of the most challenging and popular problem in nowadays society. Overweight and obesity are connected with chronic complications, such as arterial hypertension, atherosclerotic cardiovascular disease and type 2 diabetes. Nonsurgical methods of weight loss were not positively conducted in significant part of obese population. It has given a chance to develop part of medicine known as bariatric surgery. Obesity is identified as an risk factor for sexual dysfunction. The aim of this article is to summarize the main findings of studies about the influence of bariatric surgery on sexual functions of obese male patients. Materials and methods: The study is based on medical articles gathered from PubMed database spanning the years 2016-2023 and article from National Institutes of Health and from Nutritionhospitalaria. The research was conducted through the analysis of keywords such as ”Obesity”, „Bariatric Surgery”, Sexual Dysfunction”, „Men”. Results: This review indicated that surgically inducted weight loss could improve sexual function in obese men. It is connected with important increase in IIEF score and serum testosteron level. It is a need for further clinical studies to explore association of sexual function after bariatric surgery.